IDENTIFIKASI FAKTOR KINERJA KONTRAKTOR YANG PALING BERPENGARUH TERHADAP KEPUASAN STAKEHOLDERS DI DINAS CIPTA KARYA ACEH - Mohammad R. Khadafi; Muttaqin Muttaqin; Anita Rauzana (Prodi Magister Teknik Sipil Unsyiah, 2019)
In the midst of increasingly fierce competition in the world of today's construction business, every construction company is required to be able to demonstrate the quality of its service so that it can excel in competition. As a company engaged in services/selling services, construction companies must have knowledge of the dimensions of service quality. There are five factors from the dimensions of service quality, namely tangible, reliability, responsiveness, assurance and empathy. If the performance can meet their expectations, the stakeholders will be satisfied and vice versa. This study aims to identify contractor performance factors that most influence stakeholder satisfaction in the Aceh Human Settlements Agency. This study used mixed methods, combining qualitative and quantitative approaches through questionnaires. The respondents are the stakeholders of the project stakeholders at Aceh Human Settlements Agency in 2016, which consists of the Budget User, Proxy of Budget User, Technical Officer (PPTK) and Technical Officer Assistant, which in total amounted to 32 respondents. Data processing methods use validity and reliability tests, while descriptive statistical analysis uses SPSS version 22 software. The results of the study showed that the contractor's performance factors that had the most influence on stakeholder satisfaction in the Aceh Human Settlements Agency were reliability factors with a mean value of 3.714, while the least influential factors were physical evidence factors with a mean value of 3.332